2022
DOI: 10.1111/papt.12416
|View full text |Cite
|
Sign up to set email alerts
|

Negative childhood events and the development of the anorexic voice: A grounded theory

Abstract: Background: Many individuals diagnosed with anorexia nervosa (AN) describe their disorder as being represented by an internal 'anorexic voice' (AV). Previous studies have identified associations between eating psychopathology and multifarious forms of adverse life experiences. Aims: This study explores the relationship between adverse experiences in childhood and the development of the AV. Materials and Methods: Twelve women who had the experience of the AV in the context of a diagnosis of AN took part in semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The findings of this study highlight some key points, such as the role of early life/ trauma in developing global shame and also how this relates to other phenomena within AN, such as the AN voice (e.g. Morrison et al (2022)). Further work is being undertaken that is investigating the interaction between global shame and self-disgust within body image.…”
Section: Research and Clinical Implicationsmentioning
confidence: 59%
“…The findings of this study highlight some key points, such as the role of early life/ trauma in developing global shame and also how this relates to other phenomena within AN, such as the AN voice (e.g. Morrison et al (2022)). Further work is being undertaken that is investigating the interaction between global shame and self-disgust within body image.…”
Section: Research and Clinical Implicationsmentioning
confidence: 59%
“…In SLE, a history of ACEs has been associated with poorer disease outcomes, greater NP involvement, and worse perceived health status [ 133 , 134 ]. On the other hand, as trauma also impacts mental health [ 135 , 136 ], patients with FEDs report experiencing more ACEs compared to the rest of the population, with severer forms of trauma being related to aggravated FED symptomatology [ 137 , 138 , 139 , 140 , 141 , 142 ]. Taken together, it appears that ACEs may trigger the development of both entities, indicating another possible route for a dual AN–jSLE diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat different from what found in the psychosis literature, where maladaptive appraisals about the voice (including voice's malevolence) are associated with distress in voice hearers (Tsang et al, 2021). A recent model to explain the development of the eating disorder voice in anorexia nervosa proposes that the eating disorder voice might provide “an antidote” to painful emotions, enabling the individual to disconnect from internalised threatening experiences (Morrison et al, 2022). This might explain the lack of association between the characteristics of the eating disorder voice and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that greater levels of perceived power, omnipotence and benevolence of the voice at the beginning of treatment predicted greater reductions in eating disorder symptoms; however, the sample size was small (14 patients). Findings add to cross-sectional and qualitative studies which document that patients' beliefs, attitudes and behavioural responses towards the voice might contribute to illness maintenance and/or recovery (Chua et al, 2022;Forsén Mantilla et al, 2018;Morrison et al, 2022;Pugh, 2016Pugh, , 2020, through the association of the voice's characteristics with core symptoms of the illness, such as negative eating cognitions, body mass index (BMI), illness duration and compensatory behaviours (Aya et al, 2019;Noordenbos & Van Geest, 2017).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation